급성 천식 발작 환자를 위한 표준치료지침의 운용 경험: 효율성과 임상 경과 - 임동우; 박경희; 문일주; 김성렬; 고범석; 박혜정; 이재현; 박중원 (Allergy asthma & respiratory disease, 2015)
Purpose: Early recognition and management of asthma attack is critical before it becomes worse. We developed critical pathway (CP) of asthma attack at Emergency Center (EC) for making undelayed decision and management of asthma attack. Methods: Acute asthma attack assessment and treatment (4AT) CP began on April 1st 2012 and recruited the patients for 18 months. This study enrolled the patients who were older than 15 years and visited EC for dyspnea and wheezing. Initial assessment was done measuring peak expiratory flow rate (PEFR), oxygen saturation (SaO2). Once CP is activated, oxygen, inhalation of short acting β2 agonist, and injection of corticosteroid were administered to the patients. Every hour after CP activated, we reassess the patients’ response and make decisions whether to admit or discharge. Results: Until January 10th 2014, 62 patients enrolled in this study. Seven patients hospitalized for asthma and 40 patients discharged. The other 15 patients were deactivated as they were diagnosed of heart failure, myocardial infarction, aortic dissection, anaphylaxis, chronic obstructive pulmonary disease and pneumonia for the causes of dyspnea. Mean Interval from EC arrival to 4AT activation was 32.6±29.1 minutes and the mean interval from 4AT activation to position decision was 254.5±302.0 minutes. Among 47 patients who were diagnosed with asthma attack, 13 patients were not aware of asthma before this attack. Forty patients were discharged at EC after management of CP. Among them, 34 patients revisited clinic, but 6 patients did not. We called back to the lost 6 patients but only 3 patients were connected. Even they visited EC due to asthma attack, 2 patients had no insight of importance of regular management and the other one promised to revisit. Conclusion: CP was successful for early management of asthma attack. However, 15% of discharged patients never show up again. So, education program about the importance of ongoing management of asthma for prevention of asthma attack is needed. KCI Citation Count: 1